A survey of the use of electronic resources in Hezekiah Oluwasanmi library, Obafemi Awolowo university, Ile-Ife, Nigeria (2013)
This paper discussed the impact of electronic information resources as an enabler of research activites in Hezekiah Oluwasanmi library, Obafemi Awolowo university, Ile -Ife, Nigeria. A structured questionnaire was used to survey the opinions of the researchers who are the regular users of the library under study. The study showed various electronic information resources available and the degress of its utilization by the researchers and postgraduate students. There is a significant influence of the level of availability of electronic information resources on utilization [F(3,79)=10,337, P<0.05]. The study also revealed that only 6.0% of respondents use e-resources frequently thus, the usuage of e-resources is still very low in the university community. Consequently, it was recommended that the library should organize teaching of information literacy skills through user education programmes.